2019
DOI: 10.1039/c8cc08287a
|View full text |Cite
|
Sign up to set email alerts
|

Degradable vinyl copolymers through thiocarbonyl addition–ring-opening (TARO) polymerization

Abstract: Radical ring-opening polymerization of a thionolactone gives degradable thioester-functional polymers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
295
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(312 citation statements)
references
References 33 publications
13
295
4
Order By: Relevance
“…An attempted free radical homopolymerization of DOT, however, failed, achieving < 1% monomer conversion after heating with AIBN in acetonitrile-d 3 at 80 °C overnight. 28 Experiments performed in the current work supported the proposed retardation but revealed that monomer conversions could be increased to up to 10% when using DMSO as solvent and larger amounts of AIBN with heating to 60 °C for several days. In order to produce a sufficient amount of DOT homopolymer, pDOT, the procedure was repeated by adding additional AIBN into the same vial (without removing the already formed polymer), degassing, and heating.…”
Section: Dot Homopolymerizationsupporting
confidence: 75%
See 1 more Smart Citation
“…An attempted free radical homopolymerization of DOT, however, failed, achieving < 1% monomer conversion after heating with AIBN in acetonitrile-d 3 at 80 °C overnight. 28 Experiments performed in the current work supported the proposed retardation but revealed that monomer conversions could be increased to up to 10% when using DMSO as solvent and larger amounts of AIBN with heating to 60 °C for several days. In order to produce a sufficient amount of DOT homopolymer, pDOT, the procedure was repeated by adding additional AIBN into the same vial (without removing the already formed polymer), degassing, and heating.…”
Section: Dot Homopolymerizationsupporting
confidence: 75%
“…This work highlights several key advantages of thionolactones over cyclic ketene acetals (the most commonly used RROP monomers) in addition to the documented stability at ambient conditions of the DOT monomer. 28 Specifically, when using N-phenylmaleimide and N-2,3,4,5,6pentafluorophenylmaleimide as comonomers, defects in the alternating sequences were mainly caused by a faster DOT incorporation leading to degradable DOT-DOT sequences, rather than nondegradable maleimide-maleimide sequences. Furthermore, maleimides can undergo a cycloaddition side reaction with cyclic ketene acetals, which causes loss of both comonomers.…”
Section: Resultsmentioning
confidence: 99%
“…Notably,t he lattice spacing of MoS 2 in the doping composites is slightly larger than literature report( 0.62 nm), which is attributed to ion intercalation. [28][29][30][31][32][33][34][35] The nitrogen-containing triazine unit in the CTF skeleton can activate the electrons around the carbon,w hich will lead to an outstanding electrochemical performance. [27] Meanwhile, interplanars pacing of 0.27 nm is in accordance with the (1 00) Based on the above,C TFs@MoS 2 -X have ac rystal p-conjugated stacking architecture and hierarchical meso-and micropores in one hybrid system;t his fine structure is facile for fast p-electron hopping,m ass transfer,a nd confinement of the MoS 2 nanoparticles to facilitate large-particle growth.…”
Section: Resultsmentioning
confidence: 99%
“…In reported 2D CTFs, highly orderedA A( fully eclipsed) stacking leads to large electrostatic coupling and charged elocalization, thus the electron can be not only delocalized effectively in the 2D plane, but also transmitted in the vertical 2D plane direction. [28][29][30][31][32][33][34][35] The nitrogen-containing triazine unit in the CTF skeleton can activate the electrons around the carbon,w hich will lead to an outstanding electrochemical performance. [36,37] More importantly,t he MoS 2 nanoparticles are tightly grown on the surfaceo fc rystal CTFs and the synergistic effect of the coordi-nation of triazine units with Mo atoms will sharplyi ncrease the catalytic active sites, accelerating the mass and charget ransfer in HER.…”
Section: Resultsmentioning
confidence: 99%
“…[21] This technique has been rejuvenated recently by the copolymerization of common vinyl monomers and such cyclic derivatives to impart (bio)degradation of conventional materials. [21] Two main cyclic monomer families emerged, the cyclic ketene acetals (CKAs) [21][22] and the thionolactones [23][24] . The non-favorable reactivity ratio between CKA and (meth)acrylates (rCKA close to 0.01 and r(meth)acrylate close to 4) [25] led to a low and non-homogeneous incorporation of the labile group in the materials.…”
Section: Introductionmentioning
confidence: 99%